Pelatihan Penggunaan Software Geogebra Bagi Guru MTSN 2 Bengkulu Tengah - Siska, Jumiati; Selviani, Diah; Asnawati, Asnawati; Saputra, Fallela Rohma; Lestari, Monica Indah (Jurnal Dehasen Mengabdi, 2024)
The proposed Community Service (PKM) is "Training and Assistance in Using Geogebra Software for MTsN 2 Central Bengkulu Teachers. This activity is carried out in order to prepare mathematics teachers' knowledge about mathematics software with the Merdeka curriculum and with the rapid development of digital information technology which is starting to enter education World. On this basis, teachers are also required to improve their abilities in the IT field in an effort to support an effective learning process in the current digital era. PKM activity partner at MTsN 2 Central Bengkulu. Teachers at these schools will be given training in using Geogebra software. The specific target to be achieved in this PKM is that mathematics teachers at these partners are able to operate Geogebra software and make Geogebra a learning medium and are able to operate computers as a learning medium so that facilities such as computer labs and others can be used by all teachers at MTsN 2 Central Bengkulu.